Penamaan Perumahan di Jalan Ciputat-Parung: Kajian Toponimi - Pratiwi, Brillianing; Hartati, Rahma Dewi (ppjbsip, 2024)
This research examines the naming of housing on Jalan Ciputat-Parung as a form of toponymy study. The aim is to describe the naming of housing and find out what aspects are used for naming. The method used is descriptive qualitative with data sources from the naming of housing on Jalan Ciputat-Parung. Data was collected through observation, interviews, documentation and literature review. The research results show that the naming of housing on Jalan Ciputat-Parung is influenced by various factors, such as landscape, language, regional name, residential category, and so on. This research shows that housing naming is not just a label, but also reflects various aspects, such as the identity of the developer, target consumers, and characteristics of the housing environment. The study of toponymy can help us understand the meaning behind housing naming and how it influences people's perceptions and preferences. AbstrakPenelitian ini meneliti penamaan perumahan di Jalan Ciputat-Parung sebagai bentuk kajian toponimi. Tujuannya adalah untuk mendeskripsikan penamaan perumahan dan menemukan aspek yang digunakan untuk penamaan. Metode yang digunakan adalah deskriptif kualitatif dengan sumber data dari penamaan perumahan di Jalan Ciputat-Parung. Data dikumpulkan melalui observasi, wawancara, dokumentasi, dan kajian pustaka. Hasil penelitian menunjukkan bahwa penamaan perumahan di Jalan Ciputat-Parung dipengaruhi oleh berbagai faktor, seperti bentang alam, bahasa, nama daerah, kategori hunian, dan lain-lain. Penelitian ini menunjukkan bahwa penamaan perumahan bukan hanya sebuah label, tetapi juga mencerminkan berbagai aspek, seperti identitas pengembang, target konsumen, dan karakteristik lingkungan perumahan. Kajian toponimi dapat membantu kita memahami makna di balik penamaan perumahan dan bagaimana hal itu memengaruhi persepsi dan preferensi masyarakat.